The association between social support and depression among patients with vitiligo in China - Ning, Xiaoying; Zhang, Yanfei; Wang, Wei; Yan, Huling (Frontiers in Psychology, 2022)
Vitiligo is a common inflammatory skin disease with profound psychosocial impacts. Depressive symptom is one of the most common mental distress. Social support has a significant impact on the psychological status of patients. The aim of this study is to investigate the depression and social support status of patients with vitiligo in China, and further explore the correlation between social support and depression. The outpatients with vitiligo were investigated face to face with SDS (Self-rating depression scale) and SSRS (Social support rate scale). The mean SDS score of the patients was 44.05 ± 6.76, which was significantly higher than Chinese norms (p = 0.000). Female patients, unmarried, disease at rapid progressive stage and skin lesions at the exposed site had higher SDS scores (all p < 0.05). The scores of total social support, subjective support, objective support and support availability were lower than Chinese norms (all p < 0.01), and all were negatively correlated with SDS scores (all p < 0.001). In conclusion, low social support is one of the risk factors for depression in patients with vitiligo in China. More support and acceptance should be given to the patients.